2005
DOI: 10.1007/s11011-005-7212-1
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Between Clinical and Minimal Hepatic Encephalopathy on the Basis of Specific Cognitive Impairment

Abstract: It is well-known that liver cirrhosis is frequently accompanied by a wide range of neuropsychiatric abnormalities, including general and specific cognitive impairment. The aim of this study was to investigate which cognitive functions are selectively compromised in Hepatic Encephalopathy (HE) and to clarify the relationship between clinically overt or nonovert HE and the different forms and degrees of decay in cognitive deficits. Twenty-two patients without overt HE and 12 patients who showed overt HE at the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…In selecting patients, we used strict criteria to exclude any risk factors for cognitive impairment. HCV patients performed significantly worse than healthy controls matched by age, educational level and depression severity on trials 1–4 and B, recognition trial and on the total score (1–5) of the RAVLT, suggesting that HCV may be associated with impaired verbal learning and memory (encoding and consolidation process). However, no significant differences were noted between the hepatitis C group and the healthy control group in the domains of psychomotor speed and attention, executive function and phonemic and semantic verbal fluency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In selecting patients, we used strict criteria to exclude any risk factors for cognitive impairment. HCV patients performed significantly worse than healthy controls matched by age, educational level and depression severity on trials 1–4 and B, recognition trial and on the total score (1–5) of the RAVLT, suggesting that HCV may be associated with impaired verbal learning and memory (encoding and consolidation process). However, no significant differences were noted between the hepatitis C group and the healthy control group in the domains of psychomotor speed and attention, executive function and phonemic and semantic verbal fluency.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that advanced forms of the disease are accompanied by overt and global cognitive deficits (hepatic encephalopathy) (3)(4)(5). In addition, researchers and clinicians have become increasingly aware of a group of HCV patients with mild liver disease that present with a less-overt pattern of neuropsychological impairment (1,(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…2 It is well established that advanced forms of the disease are accompanied by overt and global cognitive deficits (hepatic encephalopathy). [3][4][5] Recently, researchers and clinicians have become increasingly aware of a group of HCV patients with mild liver disease that present with a less overt pattern of neuropsychological impairment. [6][7][8][9][10][11] The cognitive process that organizes simple ideas, behaviors and affects into complex actions, the one best action for the environmental cue, and the right step for the goal is called the executive function.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, HCV infection itself is associated with extrahepatic complications that may have an additional impact on the quality of life of patients with hepatitis C . One extra-hepatic manifestation, in advanced forms of the disease, is hepatic encephalopathy that can result in a broad number of cognitive deficits [Weissenborn et al, 2001;Pantiga et al, 2003;Mattarozzi et al, 2005]. Recently, many studies have found that patients infected with HCV, even in the absence of clinically significant liver disease, often complain of fatigue, depression, forgetfulness, and difficulty concentrating [Forton et al, 2002;Hilsabeck et al, 2002;Weissenborn et al, 2004Weissenborn et al, , 2005Collie, 2005;McAndrews et al, 2005].…”
Section: Introductionmentioning
confidence: 99%